Characterization of 15 microsatellite loci and genetic analysis of Heterodera schachtii (Nematoda: Heteroderidae) in South Korea. (February 2016) - Kim, Jiyeon; Kim, Taeho; Lee, Yu-Cheol; Chun, Jae-Yong; Kern, Elizabeth M.A.; Jung, Jongwoo; Park, Joong-Ki
Abstract: Heterodera schachtii, the sugar beet cyst nematode, is a major pest of agricultural crops worldwide. We report the development of fifteen polymorphic microsatellite markers and assess the genetic diversity and structure of three populations following a recent invasion of a previously unaffected region. Populations had low levels of heterozygosity, likely indicative of population structure, history, and inbreeding. Genetic diversity analysis suggested that the current infestation in South Korea may have come either from a single source population of mixed ancestry, or from multiple sources, indicating that implementing adequate prevention measures is still an unmet challenge. Much more work is needed on this species to identify global patterns of spread, and the microsatellite loci we develop here should be useful in many regions for modeling range expansion, studying the evolution of resistance, and increasing the effectiveness of pest management strategies. Highlights: We developed 15 microsatellites for the invasive nematode Heterodera schachtii. Genetic structure and diversity and spread within South Korea were examined. Detection of 2 genetic clusters suggests the possibility of multiple introductions. Populations had low heterozygosity, similar to other studies of H. schachtii. Taebaek, Gangwon Province is confirmed as the first point of invasion.